Design and implementation of asterisk in LAN for UP (DIAL UP) - Camerino, Alan Josef (2007)
One of the emerging technologies today is Voice over IP (VoIP) which uses IP networks to carry out voice applications such as telephone calls and videoconferencing. In line with this, there is an open source private branch exchange (PBX) software called Asterisk that allows VoIP to be implemented. Asterisk supports a plethora of VoIP protocols such as H.323, IAX and Session Initiation Protocol (SIP). For our research titled, Design and Implementation of Asterisk in LAN for the University of the Philippines (DIAL UP), we plan to utilize the capabilities of Asterisk as a SIP server and SIP itself by creating 3 applications: phone and video conference over Asterisk, instant messaging and collaborative whiteboard. This would be primarily implemented and tested in the local area network of the Undergraduate Thesis Laboratory with plans to expand testing to include other SIP clients on the university-wide VOIP network.